The Habermas-Rawls debate - Finlayson, James Gordon (Columbia University Press, 2019)
In the 1990s, Jürgen Habermas and John Rawls had a famous exchange in the Journal of Philosophy. In this book, James Gordon Finlayson examines the Habermas-Rawls debate in context and considers its wider implications